Vehicle Tracking to Determine Position in The Parking Lot Utilizing CCTV Camara - Suheryadi, Adi; P, Willy Permana; PY, Reza; Sumarudin, A; Firdaus, Firdaus (JOIN (Jurnal Online Informatika), 2021)
Traveling to a place using a private vehicle is an activity that many people do when visiting an area. The visitors leave their cars in several parking lots within a certain period. The resulted, them having difficulty finding vehicles in the parking lot. This study aims to assist parking service users in finding cars parked at the parking location using CCTV cameras. Apart from being used as a security system, cameras have installed in the parking lot can also be used to track the visitor's cars to the point where they park. The proposed method consists of three large blocks: background subtraction, vehicle recognition, and vehicle tracking. Results this study obtained in the test include the accuracy for the vehicle tracking process of about 91.5%, with a true positive rate of approximately 81.12%, and vehicle recognition about 70%.